Effectiveness of Giving Dragon Fruit on Increasing Hemoglobin Levels in Pregnant Women with Mild Anemia at Jakarta Harbor Hospital in 2024 - Futriani, Elfira Sri; Wijayanti, Tutik Prima; Susanti1, Tri; Toyibah; Ernawati; Astuti, Ersi (Postgraduate, University of Mataram, 2024)
Research conducted at Jakarta Harbor Hospital in 2024 aimed to evaluate the effectiveness of dragon fruit in increasing hemoglobin levels in pregnant women with mild anemia. Anemia is a common condition at the hospital, affecting around 30% of pregnant women in 2022. The study involved 36 third-trimester pregnant women with anemia. Hemoglobin levels were measured using a digital Hb meter (Quick Check), blood lancet, and strip. Data were analyzed using univariate and bivariate methods. The paired sample t-test was applied if the data followed a normal distribution, while the Wilcoxon test was used for non-normal distributions. After 14 days of administering dragon fruit, the study found an average increase in hemoglobin levels of 0.538 g/dL. This indicates that dragon fruit is effective in raising hemoglobin levels in pregnant women with mild anemia.